Enerji ihalelerinde işletme hakkı devri - Şahiner, Seyhan (My University, 2003)
TEZ ÖZETİ Birey ya da toplulukların gücünün yetmediği alanlarda Devlet tarafından yapılan ve kar elde etme amacı gütmeyen ve fakat belli bir bedel karşılığı da olabilen, toplumun ortak ve genel ihtiyacına yönelik olarak yürütülen faaliyetler kamu hizmeti kavramı olarak karşımıza çıkmaktadır. Kavramın, herkes tarafından kabul edilebilen ortak bir tanımının yapılabilmesi bu güne değin mümkün olamamakla beraber, ortak unsurların kullanıldığı bir çok tanım yapılmıştır. Kamu hizmeti anlayışıyla yürütülen faaliyetlerden bazılarının zamanla özel kişilere gördürülmesi öngörülmüş ve bu konuda çeşitli modeller geliştirilmiştir. Bunlardan örneğin, yap- işlet- devret modeli ile çalışmamızın konusunu oluşturan işletme hakkının devri modeli, aslında finansman kaynağı olarak görülmüş ve geliştirilmiş bir model olarak karşımıza çıkmaktadır. Değişen politik ve ekonomik sistemler ve bunun sonucu oluşturulan stratejiler Devlet tarafından yürütülen faaliyetlerin özel kesimce yapılmasını emretmiştir. Bu doğrultuda, ülkemizde de özelleştirme kavramı siyasal, hukuk ve ekonomi literatürümüze girmeyi başarmış ve 1980'lerden sonra da özelleştirme bir yaşam biçimi ve ekonomik zorunluluk olarak dayatılmıştır. Çalışmamız işte bu noktada ve işletme hakkı devri modeline ilişkindir. Burada, öncelikle, kamu hizmeti kavramı incelenmiş ve kamu hizmeti kavramından özelleştirme kavramına geçiş süreci üzerinde kısaca durularak özelleştirme kavram ve yöntemlerine değinilmiştir. Birinci bölümü oluşturan bu konulardan sonra, ikinci bölümde enerji ihalelerinde işletme hakkı devri konusu işlenmiştir. Burada, işletme hakkı devri sözleşmesinin yapılması, sözleşmenin hukuksal niteliği üzerinde durularak, uygulamada işletme hakkı devrinin nasıl gerçekleştirildiği anlatılmaya çalışılmıştır. Özellikle de, işletme hakkı devir bedelinin tespit usulleri ile tarifesi üzerinde durularak kimi sorunlar irdelenmeye çalışılmıştır. Çalışmamızın son kısmında, 2001 yılında yürürlüğe giren 4628 sayılı Enerji Piyasası Kanunu genel olarak irdelenmiş, burada da özellikle bu Yasa kapsamında işletme hakkı devir modelinin uygulanabilirliği, geçici maddelerde getirilen düzenlemelerle birlikte değerlendirilerek, konu tez çalışmamız açısından irdelenmeye çalışılmıştır.

OF THE PAPER What we first see in our study is that the concept of public service is not a concept of static administrative law. Especially the principle that public services are free of charge has changed. Thus, the principle where public services are charged has been adopted. However, this charge will never be determined according to the principle of having a profit. Along with the changed approach, the public sector has started to transfer many activities that it carried out to the private sector. To this end, transfer of operating rights which was formed as the result of privatization studies and is regarded as a financing model is a privatization model that foresees transfer of the establishments of the state or other public legal persons to the private persons to be operated for a definite period and in return for a charge provided that the ownership right is reserved. In this model, unlike build-operate-transfer, there is no 'build' component. This model may be expressed as 'take over-operate-transfer'. Transfer of operating rights has been treated under the scope of the Law numbered 3096 so far. Contracts of transfer of operating rights were, by nature, subject to the administrative law of the administration and both the Council of State and the Constitiutional Court had approved that these contracts are concessionaire contracts. However, this became invalid by an amendment in the Constitution in 1999 to a great extent. That is to say, now that it will be possible for the contracts that will be signed due to this model to be signed as a special law contract. In this case, the approach that when the contracts are removed from the duty field of the Council of State, they will not be supervised and perhaps the jurisdiction will be eliminated which was mentioned before the amendment particularly in the analysis carried out in the cancellation case issued by the Constitutional Court in relation to the Law numbered 3996 has been becoming null. Because the contract of transfer of operating right signed as the special law contract will be under the supervision of the Council of State. Only the place of responsible jurisdiction is changed here and this situation complies with the Law. Another issue in our study was that the contracts including the transfer of operating right is about the transfer of a public service and therefore the principles regarding public service apply to here as well. The purpose here is generally providing the public interest. Because, whether the principle of public interest could be fulfilled has been considered in the judicial analyses and decisions made regarding the transfer of operating rights. The decision of the Council of State about AKTAŞ has been a suitable example of this situation. Today, along with the enforcement of the law numbered 4628, a new energy market is aimed and the model of transfer of operating rights within the scope of privatization will be removed from the competence of the Ministry of Energy and Natural Resources and given to the Department of Privatization Administration. In practice, we cannot say that the state is successful in the transfer of operating right which we often come accross in the example AKTAŞ. Bacause, neither supervision function of the Ministry was fulfilled, nor public interest was considered during the establishment phase of signing of the contracts. Apart from this, there has been no definite prevailing rule during determination of both the tariffs and the fee of transfer of operating right; these activities were carried out unconsciously. Therefore, the concessionaire contract signed with AKTAŞ was cancelled by the Council of State and the operation was confiscated by TEDAS and take over studies have commenced. In brief, we may say that the transfer of operating right regarded as a privatization method could not be fulfilled with success in our country.
Keywords: Kamu Hizmeti; Özelleştirme_Türkiye